Evli Kadının Münhasıran Bekârlık Soyadını Kullanabilmesi - Oruç, Murat (Türkiye Adalet Akademisi, 2016)
Çalışmamızda, son dönemde oldukça yoğun gelişmelerin yaşandığı evli kadının soyadı konusu incelenmiştir. Bu bağlamda öncelikle evli kadının soyadına ilişkin hükmün gelişimi ele alınmış ve düzenlemenin olumsuz yanlarına dikkat çekilmiştir. Daha sonra, Avrupa İnsan Hakları Mahkemesi, Anayasa Mahkemesi ve Yargıtay’ın, düzenlemeyle ilgili verdikleri kararlar ele alınmıştır. İncelemenin son kısmında, yargı mercilerinin içtihatları ile ortaya çıkan “evli kadının münhasıran bekârlık soyadını kullanmasına izin verilmesi davası” tetkik edilmiştir. Anılan başlık altında, davaya ilişkin genel bir izahat verildikten sonra, davanın tarafları, yetkili ve görevli mahkeme, yargılama masrafları ve kararın hukuki sonucu ele alınarak çalışma sonlandırılmıştır.

In our study, last name of a married woman has been analysed in which there have been many developments recently. In this context, primarily, the evolution of the verdict in relation to the last name of a married woman is discussed and negative sides of the regulation are pointed out. Following to that, the verdicts of European Court of Human Rights, The Constitutional Court and the Supreme Court have been analysed. In the last section of the study, the lawsuit of permission for the exclusive use of the maiden name during marriage which emerged by the practices of judicial authorities is viewed. Under the foregoing, parties of the lawsuit, competent courts and jurisdiction, judicial costs and the legal outcome of the verdict are explained after giving a brief explanation with regards to the lawsuit itself.
Exclusive Use of a Maiden Name of a Married Woman
Keywords: Evli Kadının Soyadı; Kadın-Erkek Eşitliği; Evli Kadının Türk Medenî Kanunu; Avrupa İnsan Hakları Mahkemesi; Anayasa Mahkemesi; Yargıtay; Last Name of a Married Woman; Equality of Woman and Man; Turkish Civil Code; European Court of Human Rights; Turkish Constitutional Court; Turkish Supreme Court